FACTORS DETERMINING DIVIDEND PAYOUT: EMPIRICAL EVIDENCE OF INDONESIAN LISTED FIRMS - Theresia Trisanti (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this study is to determine the influences of the company variables to dividend policy of firms. There are four hypotheses draw for this study to increase our understanding of the effect and relationship of dividend payout of firms, such as: sales, profit, debt, and assets growth. The data used were the financial reports of each sample company which obtained through DataStream and IDX from 2010 - 2012. Four hypotheses, which relate to dividend payout such as sales, assets growth, profitability and debt financing, are tested in this research. Regression analysis indicated that profitability, sales and assets growth have positive significant influence to dividend payout but debt has negative significant. Keywords: dividend payout, sales, assets growth, profitability and debt financing.